1992
DOI: 10.1063/1.462714
|View full text |Cite
|
Sign up to set email alerts
|

Electronic polarizabilities, potential functions, and spectroscopic constants for diatomic molecules of alkali halides and alkali hydrides

Abstract: The two different approaches for the evaluation of molecular state electronic polarizabilities of ions based on Seitz–Ruffa (SR) energy level analysis and Wilson–Curtis–Coker model are critically analyzed by calculating the values of dipole moments within the framework of the original Rittner and the modified T-Rittner models. It is found that the polarizabilities based on SR energy level analysis along with the T-Rittner model are distinctly superior. These polarizabilities are used for determining spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
32
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 55 publications
3
32
0
Order By: Relevance
“…3,10,11 But the original approach of Pauling to calculate ionic R is based on the second-order Stark effect on H-like systems where the many-body effects are not included explicitly. 14 It is now realized that correlation must be included.…”
mentioning
confidence: 99%
“…3,10,11 But the original approach of Pauling to calculate ionic R is based on the second-order Stark effect on H-like systems where the many-body effects are not included explicitly. 14 It is now realized that correlation must be included.…”
mentioning
confidence: 99%
“…There has been considerable interest in the spectroscopic properties of monohalides such LiBr [1], BBr [2] and HBr [3] in the past several decades. A great amount of experimental and theoretical work has been done to obtain their spectroscopic parameters and molecular constants.…”
Section: Introductionmentioning
confidence: 99%
“…For evaluating ion in crystal polarizabilities it was thus suggested that w f be replaced by a potential dependent function. Shanker et al 3,4 extended this approach in an effort to estimate molecular state polarizabilities ␣ A or ␣ B for cation (A ϩ ) and anion (B Ϫ ) in a (A ϩ -B Ϫ ) diatomic molecule. The respective polarizabilities were represented by the expressions…”
Section: Introductionmentioning
confidence: 99%
“…This idea has subsequently been applied by a number of workers in calculating polarizabilities in studies of both crystalline 2,5 and molecular 4,6 states. A brief review of this approach may be found in the 1992 paper by Kumar and Shanker.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation